2020
DOI: 10.1002/cam4.2821
|View full text |Cite
|
Sign up to set email alerts
|

Density of breast: An independent risk factor for developing breast cancer, a prospective study at two premium breast centers

Abstract: Background: Breast cancer is the leading cause of death among women worldwide.Studies have identified breast density as a controversial risk factor of breast cancer.Moreover, studies found that breast density reduction through Tamoxifen could reduce risk of breast cancer significantly. To date, no study on the association between breast density and breast cancer has been carried out in Malaysia. If breast density is proven to be a risk factor of breast cancer, intervention could be carried out to reduce breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…who described an association of dietary fat with breast cancer risk. The current study revealed that dense breast is a risk factor for cancer breast, this is in agreement with the results of the study of Chia Hwee Lo et al (13) in (2020) showing that: Postmenopausal women with dense breasts are 3 times more likely to develop breast cancer compared to those with low breast density. The study concluded that at least 5 years history of contraceptive pills or any other hormonic drugs (therapy) intake can be a risk factor for breast cancer this is in accordance with the study of Nicole D. White et al (14) who concluded that: evaluations of contemporary hormonal contraceptive formulations support previous ndings of an approximately 20% increased risk of breast cancer for women who are using or have recently used hormonal contraception, this risk may increase with duration of use and persist for up to 5 years in women who have used hormonal contraception for at least 5 years.…”
Section: Discussionsupporting
confidence: 93%
“…who described an association of dietary fat with breast cancer risk. The current study revealed that dense breast is a risk factor for cancer breast, this is in agreement with the results of the study of Chia Hwee Lo et al (13) in (2020) showing that: Postmenopausal women with dense breasts are 3 times more likely to develop breast cancer compared to those with low breast density. The study concluded that at least 5 years history of contraceptive pills or any other hormonic drugs (therapy) intake can be a risk factor for breast cancer this is in accordance with the study of Nicole D. White et al (14) who concluded that: evaluations of contemporary hormonal contraceptive formulations support previous ndings of an approximately 20% increased risk of breast cancer for women who are using or have recently used hormonal contraception, this risk may increase with duration of use and persist for up to 5 years in women who have used hormonal contraception for at least 5 years.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, less than 10% of breast cancers can be attributed to an inherited genetic mutation, particularly if they carry mutations in the BRCA1 or BRCA2 genes [ 6 ]. However, breast cancer is more commonly linked to environmental, mainly reproductive, and lifestyle factors (i.e., obesity, alcohol consumption) [ 7 , 8 ] in addition to hormonal influences, reproductive history [ 9 , 10 ], personal health history, age, gender, race, and breast density, collectively contributing to the multifaceted nature of breast cancer risk [ 11 , 12 ]. Furthermore, breast cancer represents various warning signs, including the appearance of a lump or mass, and skin alterations like redness, puckering, or dimpling [ 13 ], unknown pain, alterations in breast size or shape [ 14 ].…”
Section: Introductionmentioning
confidence: 99%